PECULIARITIES OF PERSONNEL MANAGEMENT IN CONDITIONS OF REMOTE EMPLOYMENT - Колодяжная, Ирина; Букрина, Екатерина (SWorldJournal, 2021)
In modern conditions of the coronavirus infection pandemic dramatically have changed life of society and functioning of the economy, including the labor market. Along with the global labor market, the Ukrainian market is faced with new challenges, the ti